(untitled) (Swiss Medical Weekly, 2020)
Heparin-induced thrombocytopenia (HIT) is an immune-mediated adverse drug effect that occurs in 0.1–5% of heparin treated patients. Management of acute HIT currently involves (1) cessation of heparin exposure, and (2) inhibition of coagulation with an anticoagulant other than heparin. Several anticoagulants can be considered for the treatment of HIT. Anticoagulant monitoring, management of drug-induced adverse events including bleeding, and therapeutic dosing schedules in selected clinical settings represent challenges to the clinician treating HIT patients. Moreover, the fact that not all registered anticoagulants are approved for HIT in Switzerland further complicates the management of HIT. The present recommendations on the anticoagulant treatment of HIT in Switzerland have been elaborated by a panel of Swiss experts belonging to the Working Party Hemostasis (WPH) of the Swiss Society of Hematology (SGH-SSH). They are intended to support clinicians in their decision making when treating HIT patients.